Pelatihan Pemanfaatan E-Commerce dalam Upaya Menumbuhkan Minat Berwirausaha bagi Siswa-siswi SMK Negeri 10 Padang - Meri Rahmania; Gustia Harini (Anotero Lembaga Scientific Pekanbaru, 2022)
Current developments make job seekers increasingly difficult so that there are many unemployed in various regions, especially in big cities like Surabaya. The existence of unemployment that causes poverty occurs because the ratio between the number of jobs needed and the total number of graduates each year is not balanced. But all of that can actually be minimized by opening new businesses or entrepreneurshipVarious innovations can be applied to various forms of business interactions. E-Commerce (Electronic Commerce) is one of the rapidly growing technologies for buying and selling goods and services through electronic networks such as the internet. E-commerce is a way of shopping online that is often used in our lives. Many people benefit from the ease of doing business through the internet. Therefore, we lecturers of Stkip Pgri West Sumatra took the initiative to carry out PKM activities as a form of a lecturer's responsibility in implementing the Tridarma of Higher Education, one of which was to serve the community in the form of transferring, transforming, and applying knowledge from within the campus to the community with the theme